Evaluation of Ribavirin-Poloxamer Microparticles for Improved Intranasal Absorption - Dipy M. Vasa; Zainab Bakri; Maureen D. Donovan; Lauren A. O'Donnell; Peter L. D. Wildfong (MDPI AG, 2021)
Ribavirin is a water-soluble antiviral compound which, owing to its inability to cross the blood-brain barrier, has limited effectiveness in treating viruses affecting the central nervous system. Direct nose-to-brain delivery was investigated for ribavirin in combination with poloxamer 188, an excipient known to enhance the absorption of drug compounds administered intranasally. Composite solid microparticles suitable for intranasal insufflation were prepared by suspending fine crystals of ribavirin in a matrix of poloxamer 188, which were cryogenically milled and characterized to ensure that ribavirin remained stable throughout preparation. In vitro diffusion of ribavirin across a semi-permeable regenerated cellulose membrane showed comparable cumulative drug release after 180 min from both fine solid particles (<20 µm) and 1:1 ribavirin:poloxamer microparticles (d50 = 20 µm); however, the initial release from polymer microparticles was slower, owing to gel formation on the membrane surface. When solid ribavirin was directly deposited on excised olfactory mucosa, either as fine drug particles or 1:1 ribavirin:poloxamer microparticles, permeation was significantly increased from microparticles containing poloxamer 188, suggesting additional interactions between the polymer and olfactory mucosa. These data indicate that for highly water-soluble drugs such as ribavirin or drugs subject to efflux by the nasal mucosa, a formulation of poloxmer-containing microparticles can enhance permeability across the olfactory epithelium and may improve direct nose-to-brain transport.